2020
DOI: 10.1016/j.jval.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Intranasal Naloxone Distribution to High-Risk Prescription Opioid Users

Abstract: Objectives: To determine the cost-effectiveness of pharmacy-based intranasal naloxone distribution to high-risk prescription opioid (RxO) users. Methods:We developed a Markov model with an attached tree for pharmacy-based naloxone distribution to high-risk RxO users using 2 approaches: one-time and biannual follow-up distribution. The Markov structure had 6 health states: high-risk RxO use, low-risk RxO use, no RxO use, illicit opioid use, no illicit opioid use, and death. The tree modeled the probability of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Even before the pandemic, opioid overdose deaths were increasing significantly [5]. Studies have also been conducted to show that the provision of naloxone kits to opioid users is cost effective [30][31][32]. As the number of opioid overdoses appears to be increasing with the pandemic, it is imperative that pharmacy professionals be trained on the importance of being proactive in their approach to offering patients naloxone kits.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the pandemic, opioid overdose deaths were increasing significantly [5]. Studies have also been conducted to show that the provision of naloxone kits to opioid users is cost effective [30][31][32]. As the number of opioid overdoses appears to be increasing with the pandemic, it is imperative that pharmacy professionals be trained on the importance of being proactive in their approach to offering patients naloxone kits.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the study by Acharya et al [26], set in the USA, showed that intervention modestly reduced overdose deaths, with an ICUR of $US56,699-76,929 (year 2018 values; $US58,400-79,237 in 2020) per QALY gained. Thus, naloxone distribution was worthwhile, assuming a WTP threshold of $US100,000 (year 2018 values; $US103,083 in 2020) [26].…”
Section: Cost-utility Analysesmentioning
confidence: 99%
“…Results of the study by Acharya et al [26], set in the USA, showed that intervention modestly reduced overdose deaths, with an ICUR of $US56,699-76,929 (year 2018 values; $US58,400-79,237 in 2020) per QALY gained. Thus, naloxone distribution was worthwhile, assuming a WTP threshold of $US100,000 (year 2018 values; $US103,083 in 2020) [26]. Both deterministic and probabilistic sensitivity analyses were performed, which considered the price of naloxone, naloxone effectiveness, the proportion of overdoses witnessed, the probability of EMS intervention, overdose risk based on the specific opioid, and overdose survival rates [26].…”
Section: Cost-utility Analysesmentioning
confidence: 99%
See 2 more Smart Citations